Strengthening Marine Ecosystem Protection through the Blue Constitution Approach in Indonesia - Nathania Permata; Nadhira Wahyu Adityarani (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Indonesia, as an archipelagic nation, possesses vast marine resources, yet faces serious threats in the form of ecosystem degradation, such as the destruction of coral reefs and mangroves, and marine pollution. These issues demonstrate that marine conservation laws are not yet fully effective in ensuring ecological sustainability. This study aims to analyze the conceptualization of the Blue Constitution in the Indonesian legal system and assess its relevance in strengthening the protection of marine ecosystems. The research method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that the concept of Blue Constitution is a development of the Green Constitution, which places the sea as part of constitutional rights and an object of state protection. However, in the Indonesian legal system, this concept has not been explicitly formulated, so its implementation remains fragmented across various sectoral regulations. Therefore, conceptual strengthening and regulatory harmonization are needed to enable the Blue Constitution to function as a normative basis for the protection of sustainable marine ecosystems.